Marketing Communication Strategy through TikTok Live Streaming in Building Consumer Trust and Engagement in the Beauty Industry: A Case Study of Bening’s Clinic Surabaya - Sabrina Indira Putri; Indah Respati Kusumasari (PT. Delitekno Media Mandiri, 2026)
The rapid development of social media has encouraged companies to utilize digital platforms as interactive marketing communication media, particularly TikTok Live, which enables real-time two-way communication between businesses and consumers. Although numerous studies have examined TikTok as a digital marketing platform, limited research has specifically explored marketing communication strategies through TikTok Live in building consumer trust and engagement within the beauty industry. This study aims to analyze the marketing communication strategy implemented by Bening's Clinic Surabaya through TikTok Live in fostering consumer interest, trust, and engagement. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation, and analyzed using SWOT analysis supported by IFAS and EFAS matrices. The findings reveal that Bening's Clinic Surabaya integrates promotional activities, educational content, direct interaction, and a soft-selling approach in its TikTok Live strategy. Real-time interaction between hosts and audiences was found to increase consumer engagement, strengthen trust, and encourage interest in the clinic's services. The novelty of this study lies in the integration of SWOT, IFAS, and EFAS analyses to evaluate TikTok Live marketing communication strategies in the beauty clinic industry.